2017
DOI: 10.1111/jav.01200
|View full text |Cite
|
Sign up to set email alerts
|

An experimental approach to the brood reduction hypothesis in Magellanic penguins

Abstract: In many bird species, eggs in a brood hatch within days of each other, leading to a size asymmetry detrimental to younger siblings. Hatching asynchrony is often thought of as an adaptive strategy, and the most widely studied hypothesis in relation to this is the ‘brood reduction hypothesis’. This hypothesis states that when food resources are unpredictable, hatching asynchrony will allow the adjustment of the brood size maximizing fledging success and benefitting parents. The Magellanic penguin Spheniscus mage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Unfortunately, there were no accoustic surveys for schooling fish stocks during the study period. However, the 2012 season seemed to be a period of low abundance of these stocks, as inferred by other schooling fish predator's diet and the poor Magellanic penguin breeding success during this breeding season …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there were no accoustic surveys for schooling fish stocks during the study period. However, the 2012 season seemed to be a period of low abundance of these stocks, as inferred by other schooling fish predator's diet and the poor Magellanic penguin breeding success during this breeding season …”
Section: Discussionmentioning
confidence: 99%
“…However, the 2012 season seemed to be a period of low abundance of these stocks, as inferred by other schooling fish predator's diet 44 and the poor Magellanic penguin breeding success during this breeding season. 45 The differences in ED to parents, and hence in food provisioning, would depend on the rate of provisioning, specifically how often each adult returns with food to feed the brood, and the amount of food The random effect structure is shown in parentheses transferred in each feeding event. The latter could be affected by the larger size of males.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of hatching asynchrony is known to influence sibling competition in many bird species (Merkling et al 2014). In Magellanic penguins, last‐hatched chicks are at a competitive disadvantage throughout the pre‐fledging period (Barrionuevo and Frere 2017). Here, we demonstrated that this disadvantage could be compensated by egg size dimorphism in favor of the last‐hatched chick, agreeing with what was reported for altricial birds (Rosivall et al 2005, Bitton et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…If the nest had been categorized as ‘control', we measured each egg (E1 and E2), marked it with the laying order and returned it to the nest. If the nest had been categorized as ‘manipulated' when E1 was laid, we measured and marked the egg and replaced it with a plaster replica (the real E1 was safely placed in a plastic container inside the colony, under a bush sheltered from the sunlight but exposed to ambient temperature (Barrionuevo and Frere 2017)). The replica eggs were made of gypsum and were the same size and shape as penguin eggs, and were accepted by all females (Wagner et al 2013, Barrionuevo 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, when the availability of food is unpredictable, birds typically lay optimistic clutches that produce optimistic broods that, in case of limited availability of resources, parents can reduce or adjust to environmental conditions ( Lack 1947 , 1954 , 1968 ). Brood reduction, however, does not occur randomly among siblings and the existence of asynchronous broods, in terms of, for instance, body size or competition skills, would facilitate brood size adjustment to environmental conditions ( Lack 1947 ; Mock and Parker 1997 ; Barrionuevo and Frere 2017 ; Hildebrandt and Schaub 2018 ). The most common way for parents of producing a brood hierarchy is to start incubation before clutch completion, which results in asynchronous hatching and broods that include nestlings of different ages and sizes.…”
Section: Introductionmentioning
confidence: 99%